Optimizing Digital Forensics for Effective Cybercrime Law Enforcement in Indonesia - Lilik Prihatini; Lasmin Alfies Sihombing; Yeni Nuraeni (Universitas Islam Sultan Agung, 2026)
This study aims to analyze the optimization of digital forensic technology in enhancing the effectiveness of cybercrime law enforcement. The research method used a descriptive-analytical qualitative approach, involving in-depth interviews with cybercrime investigators, digital forensic experts, and legal practitioners, as well as documentation studies and non-participatory observations in digital forensic laboratories. The data were analyzed using an interactive analysis model to ensure the validity and reliability of the findings through triangulation techniques. The novelty of this research lies in its focus on the practical integration of digital forensic technology within law enforcement processes, particularly in examining the relationship between technological capability, human resource competence, and regulatory readiness in supporting cybercrime investigations. The findings reveal that the effectiveness of law enforcement is strongly influenced by the quality of digital evidence handling, the availability of standardized forensic procedures, and cross-sector collaboration among institutions. Furthermore, this study identifies those technological disparities, limited institutional capacity, and the lack of continuous training programs significantly affect the consistency and accuracy of investigation outcomes. Based on the research, it is concluded that optimizing digital forensic technology requires strengthening institutional capacity, improving investigator competence, enhancing infrastructure, and developing more responsive and integrated legal frameworks to ensure effective, accountable, and sustainable cybercrime law enforcement.